2013
DOI: 10.1016/j.telpol.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum sharing in the gray space

Abstract: There has been considerable effort to let more wireless devices operate in "white space" spectrum, i.e. within frequency bands and geographic areas where no wireless devices are active. Making white space available is certainly useful, but there are other sharing opportunities as well, some of which have been obscured by dangerous misconceptions about the concept of "unused spectrum." This paper discusses allowing more devices to operate safely in "gray space" spectrum, i.e. spectrum that is actively being use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Moreover, results in [11], [12] showed that a predictable rotation pattern can further enhance the sharing opportunities for the secondary users. Some of these results were employed to identify initial policy reforms needed to facilitate the implementation of vertical spectrum sharing in the radar bands [29]. These previous investigations mainly targeted technical challenges while the regulatory policies to enable large-scale secondary access in the radar bands remains still underdeveloped.…”
Section: A Related Workmentioning
confidence: 99%
“…Moreover, results in [11], [12] showed that a predictable rotation pattern can further enhance the sharing opportunities for the secondary users. Some of these results were employed to identify initial policy reforms needed to facilitate the implementation of vertical spectrum sharing in the radar bands [29]. These previous investigations mainly targeted technical challenges while the regulatory policies to enable large-scale secondary access in the radar bands remains still underdeveloped.…”
Section: A Related Workmentioning
confidence: 99%
“…Even with an adequate margin, gray space sharing inherently introduces some risks that are not presented with white-space sharing, e.g., the power control mechanisms in a secondary system might be hacked and made to interfere with the primary system, or some system bug might cause a secondary transmitter to inaccurately calculate ˜ , . To mitigate the effects of interference in such cases, a new approach to regulation and governance is required, which is beyond the scope of this paper, but discussed in [6], [16].…”
Section: Secondary Maximum Allowable Transmit Powermentioning
confidence: 99%
“…For sensitivity analysis, the ranges of parameters considered -7] dB, adapted from [14]; d) radar rotating period ˠ in [4,6] s [13]. Fig.…”
Section: A Scenariomentioning
confidence: 99%
See 2 more Smart Citations